Preface to special issue on miscellaneous emerging security problems - Chen, Kai; Shao, Jun (EAI Endorsed Transactions on Security and Safety, 2015)
An introduction to the key topics and challenges in Botnet, buﬀer overﬂow vulnerability, privacy-preserving and others.